Our best negotiators are humble people… - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2014)
In this post on the Kluwer Mediation Blog, some excerpts from the interview with one of Hong Kong’s leading police negotiators, Dr. Gilbert Wong, about his work as a crisis negotiator and his lessons for life and business are presented.